Corrigendum: Electrically-evoked responses for retinal prostheses are differentially altered depending on ganglion cell types in outer retinal neurodegeneration caused by Crb1 gene mutation (vol 17, 1115703, 2023) - Roh, Hyeonhee; Otgondemberel, Yanjinsuren; Eom, Jeonghyeon; Kim, Daniel; Im, Maesoon (Frontiers Media S.A., 2024)
In the published article there was an error in Figure 5. The title of every X-axis in Figure 5 was written incorrectly as “Light Response Firing Rage (Hz).” The correct title of every X-axis in Figure 5 should be “Light Response Firing Rate (Hz).” The corrected Figure 5 appears below: